2021
DOI: 10.1007/s00405-021-06971-7
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life after transoral CO2 laser posterior cordotomy with or without partial arytenoidectomy for bilateral adductor vocal cord paralysis

Abstract: Objectives Bilateral adductor vocal cord paralysis (BAVCP) is a rare and challenging condition whose main consequence is reduction of airway patency at the glottic level, often causing respiratory distress, while vocal function tends to remain almost normal. We investigated the effect of transoral glottal widening on quality of life and decannulation rates in patients affected by BAVCP. Methods We retrospectively evaluated patients affected by BAVCP and tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…Etiologies of BVCP were available in 36 papers (Table 1). 18‐54 Surgical procedures were known for a long‐time as responsible for most of the cases of BVFP. The data of studies were pooled to highlight the main etiologies of BVFP (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Etiologies of BVCP were available in 36 papers (Table 1). 18‐54 Surgical procedures were known for a long‐time as responsible for most of the cases of BVFP. The data of studies were pooled to highlight the main etiologies of BVFP (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…The data of studies were pooled to highlight the main etiologies of BVFP (Table 1). 18‐54 Surgery (76.6%), idiopathic (6.9%), traumas (3.0%), and neurological diseases (2.5%) are the most common causes of BVFP. The surgical procedures associated with an increased risk of BVFP include thyroidectomy (97.1%), 18‐25,27,28,31‐54 esophagectomy (1.4%), 18,25,27 brain or skull base surgeries (0.7%), 28,31 tracheal or chest surgeries (0.6%), 25,48 bilateral glomus resection (0.1%), 52 and thymectomy (0.1%) 36 .…”
Section: Resultsmentioning
confidence: 99%
“…The purpose of BVFP treatment is to create an appropriate airway, maintain voice quality, and avoid aspiration, studies showed that posterior cordotomy was a commonly performed and effective technique with a short operation time in patients with BVFP. 3,6,8,14,15 The anterior 2/3 of the vocal fold is membranous, which is mainly responsible for vocal functions, and the posterior 1/3 is the cartilaginous part, the main function of which is respiration. Posterior cordotomy preserves the membranous part of the vocal fold and enlarges the cartilaginous glottis to minimise the impact on vocal function.…”
Section: Discussionmentioning
confidence: 99%
“…Posterior cordotomy preserves the membranous part of the vocal fold and enlarges the cartilaginous glottis to minimise the impact on vocal function. 16 However, a revision operation is frequently required in patients with posterior cordotomy, 3,6,8,17 the possible reason is granulation tissue and scar tissue will first fill the cordotomy defect. Segas et al 18 reported that the respiratory success rate of posterior cordotomy is 50%-68% in the first procedure, and 90%-100% in the second procedure, and partial arytenoidectomy or its combination with posterior cordectomy indicated an even higher rate of successful decannulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation